Understanding the impact of summer festival on the dynamic of micropollutant delivery to coastal wastewater treatment plant - Agne Jucyte-Cicine; Elise Lorre; Jolita Petkuviene; Zita R. Gasiunaite; Ema Durcova; Irma Vybernaite-Lubiene; Mindaugas Zilius (Emerging Contaminants)
Coastal cities often experience a surge in population during summer events, leading to heightened pollution entering wastewater treatment plants (WWTPs). However, the impact of these events on wastewater treatment effectiveness and the levels of hazardous substances passed into coastal ecosystems remain poorly understood. This study investigated wastewater quality and specific micropollutants (estrogens, pharmaceuticals, phthalates (PAEs), polycyclic aromatic hydrocarbons) both before and after treatment at WWTP during the summer festival at the south-eastern Baltic coastal city. The results revealed that influent flow, nutrient and pollutant loads, except for pharmaceuticals, increased during the festival. Notably, the load of specific organic pollutants (dissolved organic carbon, estrogen, and PAEs) increased by ∼50 %, which is more than three times the increase in influent flow. Despite this, the treatment process achieved high retention rates between 87 % and 100 %. Nevertheless, the overall effectiveness of the treatment process, the estrogen level in discharged effluents into the sea exceeded the environmental quality standard limits 7–12 fold. Pharmaceuticals and PAEs contributed most to the micropollutant load (25 g day−1 and 34 g day−1, respectively) discharged into the Baltic Sea during the festival. These findings provide novel insights into how temporal gatherings can increase pollution levels in the coastal areas of the Baltic region and highlight the potential for this pollution to be inadequately retained in treatment facilities, posing risks to the marine environment.